The Relationship Between Breakfast Habits and Frequency of Snack Food Consumption with the Nutritional Status of Students at SMA Negeri 4 Surakarta - Zahra Dhiya'an Almas Putri Kinasih; Muwakhidah; Farida Nur Isnaeni (STIKes Budi Luhur Cimahi, 2026)
Adolescent nutritional status is influenced by multiple dietary behaviors, including breakfast habits and snack food consumption. This study aimed to examine the association between breakfast habits and snack consumption frequency with the nutritional status of students at SMA Negeri 4 Surakarta. An observational analytic study with a cross-sectional design was conducted among 100 students in grades X and XI, selected using stratified proportional random sampling. Breakfast habits were assessed using a 3-day food record and categorized as regular (consuming breakfast ≥5 days per week) or irregular (<5 days per week). Snack food consumption was measured using a food frequency questionnaire (FFQ) and classified as frequent (≥1 time per day) or infrequent (<1 time per day). Nutritional status was determined using Body Mass Index-for-Age (BMI-for-age) based on WHO standards. The results showed that 79% of students had regular breakfast habits, while 21% had irregular habits. Snack consumption was equally distributed, with 50% categorized as frequent consumers and 50% as infrequent consumers. In terms of nutritional status, 8% of students were underweight, 74% were normal, and 18% were overweight. Chi-square analysis revealed a significant association between breakfast habits and nutritional status (p = 0.021, Cramér’s V = 0.32), as well as between snack consumption frequency and nutritional status (p = 0.034, Cramér’s V = 0.28). In conclusion, both breakfast habits and snack consumption frequency are significantly associated with the nutritional status of high school students. These findings underscore the importance of promoting regular breakfast consumption and healthy snacking behaviors to support optimal adolescent nutrition.